(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The paper describes algorithms and structure of the electro-friction interaction synergetic model. The results of theoretical modelling and experimental study of sliding electrical contact are given. The comparison of theoretical and experimental results made in the paper proves high validity of the model and its programmatic implementation.